2015
DOI: 10.1002/ajhb.22784
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between height increase and LDL cholesterol during puberty: A 3‐year follow‐up study of the Fukuroi City

Abstract: Serum LDL-C decreased with increasing height, independent of increases in weight. The association between LDL-C and height is stronger than that between LDL-C and weight. Am. J. Hum. Biol. 28:330-334, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The Bogalusa Heart Study reported that changes in height for five years in boys were inversely correlated with TC, LDL-C, and HDL-C levels 12 (9). This negative correlation between the LDL-C concentration and growth rate in both boys and girls was also supported by the findings of large-scale prospective study conducted in Japan 14 . Finally, a recent study of 6,300 adolescents conducted by the West Virginia Coronary Artery Risk Detection in Appalachian Communities (CARDIAC) project reported that the risk of hyper-LDL-cholesterolemia increases significantly in the first (shortest) quartile stature compared with that in the fourth (tallest) quartile stature (OR = 1.3~3) 15 .…”
Section: Discussionsupporting
confidence: 67%
“…The Bogalusa Heart Study reported that changes in height for five years in boys were inversely correlated with TC, LDL-C, and HDL-C levels 12 (9). This negative correlation between the LDL-C concentration and growth rate in both boys and girls was also supported by the findings of large-scale prospective study conducted in Japan 14 . Finally, a recent study of 6,300 adolescents conducted by the West Virginia Coronary Artery Risk Detection in Appalachian Communities (CARDIAC) project reported that the risk of hyper-LDL-cholesterolemia increases significantly in the first (shortest) quartile stature compared with that in the fourth (tallest) quartile stature (OR = 1.3~3) 15 .…”
Section: Discussionsupporting
confidence: 67%
“…3,4 Accordingly, search has begun for a simple indicator to access obesity-related metabolic risks that should be practical and cost-effective to measure, more sensitive than BMI and WC, and with a universal cut-point for both sexes and subjects of different ethnic groups. Some have suggested the WC/height (WC/H) ratio as an indicator of obesity-related health risks, hypothesizing that since shorter subjects tend to have a higher risk of developing abnormalities (metabolic syndrome and related diseases 9,10 ), height should be taken into account when WC is used as a putative obesity marker. 11 Some studies among adults have demonstrated that the WC/H index is useful as a screening tool for obesity and related metabolic disorders, 6,12,13 and a cut-point of 0.5 seems to be a suitable boundary value to identify subjects at risk of metabolic disorders, independent of sex and ethnicity.…”
mentioning
confidence: 99%
“…The odds ratio of dyslipidemia (LDL > 140 mg/dl or triglycerides 150 mg/dl) fell from the first (shortest) to fourth (tallest) quartile in those under 25 kg/m 2 , but was nonsignificant for those 25 kg/m 2 . Fujita et al measured lipids in 2,515 students in public schools in Fukeroi, Japan, from 2008 to 2010 and then again in the eighth grade with follow-up in 2,225 students (9). Lipid levels decreased in association with largest increased height over 3 years, but this was attenuated in the group with a larger weight increment.…”
mentioning
confidence: 99%